Biomarkers of Oxidative Stress and Endogenous Antioxidants for Patients with Chronic Subjective Dizziness - Fang, Zhigang; Huang, Keer; Gil, Chang-Hyun; Jeong, Jin-Woo; Yoo, Ho-Ryong; Kim, Hyeong-Geug (Scientific reports, 2020)
As a neurotologic disorder of persistent non-vertiginous dizziness, chronic subjective dizziness (CSD) arises unsteadily by psychological and physiological imbalance. The CSD is hypersensitivity reaction due to exposure to complex motions visual stimuli. However, the pathophysiological features and mechanism of the CSD still remains unclearly. The present study was purposed to establish possible endogenous contributors of the CSD using serum samples from patients with the CSD. A total 199 participants were gathered and divided into two groups; healthy (n = 152, male for 61, and female for 91) and CSD (n = 47, male for 5, female for 42), respectively. Oxidative stress parameters such as, hydrogen peroxide and reactive substances were significantly elevated ( p < 0.01 or p < 0.001), whereas endogenous antioxidant components including total glutathione contents, and activities of catalase and superoxide dismutase were significantly deteriorated in the CSD group ( p < 0.01 or p < 0.001) as comparing to the healthy group, respectively. Serum levels of tumor necrosis factor -α and interferon-γ were significantly increased in the CSD participants ( p < 0.001). Additionally, emotional stress related hormones including cortisol, adrenaline, and serotonin were abnormally observed in the serum levels of the CSD group ( p < 0.01 or p < 0.001). Our results confirmed that oxidative stress and antioxidants are a critical contributor of pathophysiology of the CSD, and that is first explored to establish features of redox system in the CSD subjects compared to a healthy population.